The Spanish livestock model: A coevolutionary analysis (Ecological Economics, 2013)
Coevolution is a wide theoretical framework that enables the study of socio-ecological transformations in different contexts and, specifically, in agrarian systems. This article analyses coevolutionary changes in Spanish livestock over the last 50 years, fromthe so-called “traditional” livestock model, in which ecological, social and economic elements co-evolve in closely interconnected relationships, to the currently dominant industrial livestock model, governed by “ecologies at a distance”. Not only meat consumption grew significantly as a consequence of the change in the prevailing livestock production model, Spain also became one of the most important meat producers in the European Union. Simultaneously, dependence on imported cereals and soya increased dramatically. Nevertheless, in spite of the prevalence of industrial logics, extensive livestock farming, that follows hybrid logics incorporating features from both models, still exists in Spain and, particularly, in Andalusia (Southern Spain). This locally based model is characterised by higher environmental standards, as well as its contribution to the preservation of a singular agro-ecosystem(dehesa). However, its long-termtrans- formation and, therefore, the social construction ofmore sustainable local livestock systems,must be understood as a co-evolutionary process in which agency and social selection of innovations are essential elements.